Peningkatan Pengetahuan Ibu-Ibu tentang Hipertensi - Sugiman Sugiman; Tedy Candra Lesmana (STIKES Wira Husada Yogyakarta, 2022)
ABSTRACTPeningkatan pengetahuan ibu-ibu tentang hipertensi.. Hypertension is an important risk factor for cardiovascular disease, which is the leading cause of death in women. Those who are at risk of developing hypertension are very important to prevent it by providing knowledge through education. The purpose of this community service activity is to increase public knowledge about hypertension. Efforts to increase knowledge of mothers about hypertension through counseling. Counseling is carried out online using the WhatsApp application. Whatsapp groups were formed consisting of community service teams and mothers. Before and after the delivery of the material, pre-test questions were given to post-test questions and the work was done using Google Form. The values obtained from the pre-test and post-test were analyzed. The material contains the understanding, symptoms, risk factors and prevention of hypertension which is presented in the form of Powerpoint slides. Discussions and questions and answers were held after the material was delivered. Mothers have a better level of knowledge after being given counseling.Keywords: Increased knowledge of mothers about hypertensionABSTRAKPeningkatan pengetahuan ibu-ibu tentang hipertensi. Hipertensi merupakan faktor risiko penting untuk penyakit kardiovaskular, yang merupakan penyebab utama kematian pada wanita. Mereka yang berisiko terkena hipertensi sangat penting untuk mencegahnya dengan memberi pengetahuan melalui edukasi. Tujuan kegiatan pengabdian kepada masyarakat ini untuk meningkatkan pengetahuan masyarakat tentang hipertensi. Upaya peningkatan pengetahuan ibu-ibu tentang hipertensi melalui penyuluhan. Penyuluhan dilaksanakan secara daring menggunakan aplikasi WhatsApp. Grup Whatsapp dibentuk beranggotakan tim pengabdian kepada masyarakat dan ibu-ibu. Sebelum dan sesudah penyampaian materi diberikan soal pre-test soal post-test dan pengerjaannya menggunakan Google Form. Nilai yang diperoleh dari pre-test dan post-tes dianalisis. Materi berisi pengertian, gejala, faktor risiko dan pencegahan hipertensi yang disajikan dalam bentuk slide Powerpoint. Diskusi dan tanya jawab dilakukan setelah materi selesai disampaikan. Ibu-ibu memiliki tingkat pengetahuan yang lebih baik setelah diberikan penyuluhan.Kata kunci: pengetahuan, hipertensi, ibu-ibuABSTRACTPeningkatan pengetahuan ibu-ibu tentang hipertensi.. Hypertension is an important risk factor for cardiovascular disease, which is the leading cause of death in women. Those who are at risk of developing hypertension are very important to prevent it by providing knowledge through education. The purpose of this community service activity is to increase public knowledge about hypertension. Efforts to increase knowledge of mothers about hypertension through counseling. Counseling is carried out online using the WhatsApp application. Whatsapp groups were formed consisting of community service teams and mothers. Before and after the delivery of the material, pre-test questions were given to post-test questions and the work was done using Google Form. The values obtained from the pre-test and post-test were analyzed. The material contains the understanding, symptoms, risk factors and prevention of hypertension which is presented in the form of Powerpoint slides. Discussions and questions and answers were held after the material was delivered. Mothers have a better level of knowledge after being given counseling.Keywords: Increased knowledge of mothers about hypertensionABSTRAKPeningkatan pengetahuan ibu-ibu tentang hipertensi. Hipertensi merupakan faktor risiko penting untuk penyakit kardiovaskular, yang merupakan penyebab utama kematian pada wanita. Mereka yang berisiko terkena hipertensi sangat penting untuk mencegahnya dengan memberi pengetahuan melalui edukasi. Tujuan kegiatan pengabdian kepada masyarakat ini untuk meningkatkan pengetahuan masyarakat tentang hipertensi. Upaya peningkatan pengetahuan ibu-ibu tentang hipertensi melalui penyuluhan. Penyuluhan dilaksanakan secara daring menggunakan aplikasi WhatsApp. Grup Whatsapp dibentuk beranggotakan tim pengabdian kepada masyarakat dan ibu-ibu. Sebelum dan sesudah penyampaian materi diberikan soal pre-test soal post-test dan pengerjaannya menggunakan Google Form. Nilai yang diperoleh dari pre-test dan post-tes dianalisis. Materi berisi pengertian, gejala, faktor risiko dan pencegahan hipertensi yang disajikan dalam bentuk slide Powerpoint. Diskusi dan tanya jawab dilakukan setelah materi selesai disampaikan. Ibu-ibu memiliki tingkat pengetahuan yang lebih baik setelah diberikan penyuluhan.Kata kunci: pengetahuan, hipertensi, ibu-ibu